Utilization of Project Kind-Er (Engagement in Reading) to Strengthen the Foundation of Learning in Kindergarten - Ricaplanca, Ma. Benilda; De Guzman, Mart Albert; Bautista, Christian (JPAIR Multidisciplinary Research, 2024)
The Kindergarten Curriculum in the Philippines (2016) recommends introducing alphabet names, sounds, and symbols during the 11th week, coinciding with the second quarter of the academic year. The curriculum initially presents two letters each week and another two in the subsequent weeks, which may challenge five-year-old pupils in comprehending the abstract nature of the alphabet. This study aimed to determine the effects of introducing one letter per week and another in the subsequent weeks, thereby creating a more engaging learning environment without overwhelming the pupils with two letters at once. The implementation began in the third week of the first quarter. A Sound-Recognize-Write assessment checklist was used in this study, involving thirty-five kindergarten pupils from a single section. The results revealed that 30 out of 35 mastered the sound, name, and symbol of all twenty–eight (28) letters in the Filipino alphabet. In this study, researchers also found out the most difficult letters to master and the easiest letters to recognize. It was then recommended that additional time be provided to explore the letters, especially those letters that are difficult to master. A 5-day activity plan was proposed to help the struggling learners to improve their literacy skills.
Keywords: Kindergarten Curriculum; sound-recognize-write checklist; assessment; 5-day activity plan; reading; Early Childhood Education